2010
DOI: 10.1017/s0022029910000816
|View full text |Cite
|
Sign up to set email alerts
|

Best combination of pre-stimulation and latency period duration before cluster attachment for efficient oxytocin release and milk ejection in cows with low to high udder-filling levels

Abstract: Experiments were designed to investigate the suitability of a combination of a short manual teat stimulation with a short latency period before teat cup attachment to induce and maintain oxytocin release and milk ejection without interruption. In Experiment 1, seven dairy cows in mid lactation were manually pre-stimulated for 15, 30 or 45 s, followed by either 30 s or 45 s of latency period. It was shown that all treatments induced a similar release of oxytocin without interruption until the end of milking. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
44
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 22 publications
9
44
1
1
Order By: Relevance
“…Milking unit on-time was shortest for HV90 (245 s) and this was significantly different (P < 0.05) from all other treatments. Kaskous and Bruckmaier (2011) indicated that lag time had no effect on milking unit on-time when proportion of udder filling was >40%; however, increasing the lag time from 0 to 30, 45, or 60 s independent of stimulation time reduced the unit on-time when the degree of udder filling was <40%. Sandrucci et al (2007) found the shortest milking unit on-time when lag times were between 1 and 60 s, whereas Watters et al (2012) reported that when the lag time was >60 s, milking unit on-time decreased in late-lactation cows.…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…Milking unit on-time was shortest for HV90 (245 s) and this was significantly different (P < 0.05) from all other treatments. Kaskous and Bruckmaier (2011) indicated that lag time had no effect on milking unit on-time when proportion of udder filling was >40%; however, increasing the lag time from 0 to 30, 45, or 60 s independent of stimulation time reduced the unit on-time when the degree of udder filling was <40%. Sandrucci et al (2007) found the shortest milking unit on-time when lag times were between 1 and 60 s, whereas Watters et al (2012) reported that when the lag time was >60 s, milking unit on-time decreased in late-lactation cows.…”
Section: Resultsmentioning
confidence: 86%
“…Milk yield per milking did not differ when comparing 60 s of manual stimulation to 60 s of vibration stimulation (Karch et al, 1988) or when comparing manual stimulation, no stimulation, and mechanical stimulation (Sagi et al, 1980b). Milk yield did not differ within classes of udder filling when comparing lag times of 0, 30, 45, and 60 s (Kaskous and Bruckmaier, 2011).…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations